Traumatic Acute Vertex Epidural Hematoma(vEDH): A Case Report - Tyngkan, Lamkordor; Laloo, Memida; Pasi, Mebanshanbor Garod (Indian Journal of Neurotrauma, 2023)
Vertex epidural hematoma (vEDH) is a rare type of intracranial hematoma, which accounts for 0.024% of all head injuries and 0.47 to 8.2% of intracranial hematoma, with high mortality rate of approximately 50% if not detected early. We report a case of 30-year-old male with fall from height presenting with headache and bradycardia. Craniotomy with complete evacuation of vEDH was done. vEDH is a relatively rare entity and in suspected case of vEDH one should always get thin cuts of computed tomography along with sagittal and coronal cuts.
Keywords: craniotomy; epidural hematoma; fall; hemostasis; vertex